Umm el-Qaab (Abydos), Ägypten. Untersuchungen zum Osiriskult in Abydos vom Alten Reich bis in die Spätantike. Die Arbeiten der Jahre 2018 und 2019 - Effland, Ute; Effland, Andreas (e-Forschungsberichte des DAI, 2019)
Intensive excavations were carried out in the early and predynastic period necropolis at Umm el-Qaab towards the end of the 19th and at the beginning of the 20th century by É. Amélineau (in 1895–1899), W. M. F. Petrie (in 1899–1901) and É. Naville and E. Peet (in 1908–1911). H. Hall in the year 1925 and W. B. Emery at an unknown date also carried out research on smaller, limited areas. During the course of these early excavations, an area of approximately 150 × 600 m in the centre of Umm el-Qaab was almost entirely turned over. In addition to the original high mounds of pottery, heaps of up to 11 m in height containing burial equipment, votive material, rubble, sherds and spoil resulted from the excavation work. In 1977, the German Archaeological Institute resumed scientific study of the site under the aegis of W. Kaiser and G. Dreyer. During the last years investigations in the secondary phase of occupation in the context of Osiride cult practices over a time period from the Old Kingdom to the mid-6th century AD was intensified. The focus of work done in 2018 and 2019 concentrated mainly on the documentation of inscribed material, small finds and pottery.